Membayar Zakat Fitri dengan Qīmah Menurut Ibnu Taimiyyah (Studi Kitab Majmū` al-Fatāwā): Paying Fitri Zakat with Qīmah According to Ibnu Taimiyyah (Study of the Book of Majmū` al-Fatāwā) - Rosmita, Rosmita; Hijrayanti Sari; Fina Afrianty (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out and understand Ibn Taymiyyah's opinion regarding zakat fitr with qīmah. The problems that researchers raise in this research are: First, what is the law on paying zakat al-Fitr with qīmah according to Ibn Taimiyyah in the book Majmū` al-Fatāwā? ; Second, what is the analysis of Ibn Taymiyyah's istinbat method regarding paying zakat fitri with qīmah? This research uses qualitative research with the aim of exploring basic theories and concepts that have been put forward by experts and to obtain a broader orientation regarding the research topic and uses a content analysis approach and a normative approach. The results of the research found are as follows: first, in Ibn Taymiyyah's view the law of paying zakat fitr with qīmah is permissible if there is a strong benefit, need and justice, but if there is no strong benefit then zakat fitr cannot be paid in the form of qīmah and it should still be paid with staple foods in accordance with the provisions of the Prophet SAW. Second, Ibn Taimiyyah uses a flexible and comprehensive istinbat method to discuss the payment of zakat al-Fitr with qīmah. Although he follows the basic principles of zakat fitri established by the hadith, he also considers the benefit, and provides guidance that is relevant to the conditions of society. His approach strikes a balance between adherence to the sunnah and adaptation to practical needs in society.